Intrahepatic Fat Content and Markers of Hepatic Fibrosis in Obese Children. (4th February 2016) - Wu, Wei; Zhang, Hongxi; Xu, Xiaoqin; Huang, Ke; Fu, Junfen
Abstract : Aim. We evaluated both direct and indirect hepatic fibrosis markers in obese children and their relationship with intrahepatic fat (IHF) content. We also aimed to investigate the possible roles of IHF and fibrosis markers in metabolic syndrome (MS). Methods. 189 obese children were divided into simple obese (SOB), simple steatosis (SS), and nonalcoholic steatohepatitis (NASH) groups according to their IHF and blood alanine transaminase (ALT) levels. They were also scored for the MS components. IHF was assessed as a continuous variable by proton magnetic resonance spectroscopy (1H-MRS). In addition, 30 nonobese children were enrolled as controls and their direct hepatic fibrosis markers and IHF were assessed. Results . Age was related to IHF, NFS, and FIB-4. Both NFS and APRI were related to IHF more significantly than the direct markers. In the estimation of liver function impairment, indirect markers had greater AUROC than direct markers. In MS, IHF and all the fibrosis markers showed similar AUROC. Conclusions . Both direct and indirect markers played a valuable role in evaluating MS. Indirect markers were more effective in distinguishing fatty hepatitis. Age is an important factor underlying hepatic steatosis and fibrosis even in children.